Catching a glimpse of the bacterial gut community of companion animals: a canine and feline perspective. Issue 6 (30th August 2020) - Alessandri, Giulia; Argentini, Chiara; Milani, Christian; Turroni, Francesca; Cristina Ossiprandi, Maria; van Sinderen, Douwe; Ventura, Marco
Summary: Dogs and cats have gained a special position in human society by becoming our principal companion animals. In this context, efforts to ensure their health and welfare have increased exponentially, with in recent times a growing interest in assessing the impact of the gut microbiota on canine and feline health. Recent technological advances have generated new tools to not only examine the intestinal microbial composition of dogs and cats, but also to scrutinize the genetic repertoire and associated metabolic functions of this microbial community. The application of high‐throughput sequencing techniques to canine and feline faecal samples revealed similarities in their bacterial composition, with Fusobacteria, Firmicutes and Bacteroidetes as the most prevalent and abundant phyla, followed by Proteobacteria and Actinobacteria. Although key bacterial members were consistently present in their gut microbiota, the taxonomic composition and the metabolic repertoire of the intestinal microbial population may be influenced by several factors, including diet, age and anthropogenic aspects, as well as intestinal dysbiosis. The current review aims to provide a comprehensive overview of the multitude of factors which play a role in the modulation of the canine and feline gut microbiota and that of their human owners with whom they share the same environment. Abstract : Dogs and cats have gained a special position in human society by becoming our principal companion animals. In this context, efforts to ensure their health and well‐fare have increased exponentially, with in recent times a growing interest in assessing the impact of the gut microbiota on canine and feline health. Recent technological advances have generated new tools to not only examine the intestinal microbial composition of dogs and cats, but also to scrutinize the genetic repertoire and associated metabolic functions of this microbial community, revealing that the taxonomic composition and the metabolic repertoire of the intestinal microbial population of dogs and cats may be influenced by several factors, including diet, age and anthropogenic aspects, as well as intestinal dysbiosis.